Multilevel Analysis on the Ecological Effect of School on the Risk of Anemia among Female High School Students in Klaten Central Java - Dewayanti, Nurmala; Sulaeman, Endang Sutisna; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: Anemia is a major nutritional problem worldwide. In 2018, at least 1.62 billion people were affected by anemia, and 33% were school children. Anemia in female ado